2016
DOI: 10.1155/2016/2515420
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of the Feasibility, Usability, and Acceptability of a Mobile Client Data App for Community-Based Maternal, Neonatal, and Child Care in Rural Ghana

Abstract: Mobile phone applications may enhance the delivery of critical health services and the accuracy of health service data. Yet, the opinions and experiences of frontline health workers on using mobile apps to track pregnant and recently delivered women are underreported. This evaluation qualitatively assessed the feasibility, usability, and acceptability of a mobile Client Data App for maternal, neonatal, and child client data management by community health nurses (CHNs) in rural Ghana. The mobile app enabled CHN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 53 publications
8
78
0
3
Order By: Relevance
“…In some facilities, they had no additional support with these tasks, and allocating such support could be difficult in overburdened and understaffed PHC facilities in resource-constraint settings. As in several other studies [42][43][44], we found that successfully maintaining an mHealth system was a challenge when added to staff's existing job descriptions. In addition, many clerks reported struggling with the technical aspects of the mHealth system.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In some facilities, they had no additional support with these tasks, and allocating such support could be difficult in overburdened and understaffed PHC facilities in resource-constraint settings. As in several other studies [42][43][44], we found that successfully maintaining an mHealth system was a challenge when added to staff's existing job descriptions. In addition, many clerks reported struggling with the technical aspects of the mHealth system.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies confirm the need for integration, claiming that it may strengthen health system functioning [39] and promote the sustainability of the mHealth system [40]. As was found in our study, poor integration may frustrate users and lead to additional labourintensive tasks for them [41,42]. With this in mind, automated entry, as suggested by the clerks, could help to ensure that staff with many other responsibilities do not have to spend time on manually issuing and closing recalls and referrals.…”
Section: Discussionsupporting
confidence: 68%
“…Research shows that adoption of technological tools by MHWs relies heavily on their perceived usability, value, security and social influence, along with the ease of tool's integration into the existing workflow [3,25]. But, steps should be taken to address the literacy levels of the health workers utilizing the equipment [21].…”
Section: Adoption and Usabilitymentioning
confidence: 99%
“…Limited‐scale implementation of applications—for data collection, clinical decision support, and follow‐up visit reminder systems—has provided valuable information regarding feasibility, usability, acceptability, and ability to promote quality data collection. Common lessons learned are the need to understand local conditions in‐depth prior to implementation, continually evaluate systems to ensure they meet user needs, and provide periodic supervision to enhance data quality and use …”
Section: Recent Advances and Promising Practicesmentioning
confidence: 99%
“…Common lessons learned are the need to understandlocalconditionsin-depthpriortoimplementation,continuallyevaluatesystemstoensuretheymeetuserneeds,andprovide periodicsupervisiontoenhancedataqualityanduse. 19,40,41 In Zambia, a system for telemedicine and quality assurance that combinesmobiletelecommunicationsanddigitalcervicographyplayed avitalroleinimprovingandscalingupvisualinspectionwithaceticacid (VIA)-based cervical cancer screening. 42,43 A similar approach using smartphonestocaptureandtransmitdigitalcervicalimageshasbeen successfullytestedinMadagascar, 44 andscaled-upinBotswana.…”
Section: Smart Use Of Mobile and Other Technologiesmentioning
confidence: 99%